Glossary of the Portuguese language of snow, ice, and related terms – Second edition - Simões, Jefferson Cardia; Rosa, Kátia Kellem da; Vieira, Rosemary; Petsch, Carina; Velho, Luiz Felipe; Carlos, Franciele Schwanck; Marquetto, Luciano; Lindau, Filipe Gaudie Ley; Ribeiro, Rafael da Rocha (Geografia Ensino & Pesquisa, 2024)
Due to the growth of Brazilian research in Antarctica and the Andes, it is necessary to expand the vocabulary of glaciological and related topics in the Portuguese language. So, this second edition revises the Glossary and doubles the number of definitions, covering 400 words related to the glacial environment. These are defined and followed by English, French, German, and Spanish equivalents. Debido al crecimiento de las investigaciones brasileñas en la Antártida y los Andes, es necesario ampliar el vocabulario glaciológico y temas afines en lengua portuguesa. Así, esta segunda edición revisa el Glosario y duplica el número de definiciones, abarcando 400 palabras relacionadas con el entorno glaciar. Estos están definidos y seguidos de equivalentes en inglés, francés, alemán y español. Devido ao crescimento das pesquisas brasileiras na Antártica e no Andes, faz-se necessário ampliar o vocabulário glaciológico e de temas relacionados na língua portuguesa. Assim, esta segunda edição revisa o Glossário e duplica o número de definições, cobrindo 400 vocábulos relacionados ao ambiente glacial. Estes são definidos e seguidos por equivalentes em inglês, francês, alemão e espanhol.